Entrepreneurship as Social Problem Solving : Case Study in Tasikmalaya - Rachmani, Nizza Nadya; Nurfitriya, Mira; Koeswandi, Tika Annisa Lestari; R, Wanda Puspa Dewi Astuti (Universitas Pendidikan Indonesia, 2023)
Social problems are problems that are contrary to the social values adopted by society, such as poverty. Tasikmalaya Regency is one of the areas that has a fairly high poverty rate. MSMEs are one way to alleviate poverty. The purpose of this study is to determine the role of MSMEs in solving social problems in Tasikmalaya Regency. The results of this study are that SMEs play a role in reducing unemployment with the comparison that 1 UMKM is able to empower 2-9 workers. In addition, MSMEs in Tasikmalaya Regency are able to reduce the number of poor people. This can be seen from the average amount of wages received by workers in the MSME sector which is above the monthly expenditure for basic needs with a ratio of IDR 3.150.572,55 to IDR 977.655 per capita.